تحليل مواد تعليم اللغة العربية لكتاب النحو الواضح في الجزء الأول لعلي الجارم ومصطفى أمين - Uqba, M Sholih Salimul; Saleh, Ummu Sulaimah; Latipah, Nur; Daroini, Slamet; Ibrahim, Faisal Mahmoud Adam (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2024)
Nahwu Wadhih is one of the most widely used Arabic grammar books among beginner Arabic language learners. Therefore, it is essential to deeply understand and study the book's background, objectives, advantages, and disadvantages. This study aims to describe the author's biography, history, and overview of the book Nahwu Wadhih First Juz by 'Ali Al-Jarim and Musthafa Amin and identify it in terms of the book's objectives, advantages, and disadvantages. This research uses a descriptive qualitative approach with the type of library research with the book Nahwu Wadhih First Juz as the primary data and several books and scientific journals as secondary data. The data collection technique was carried out using the documentation method, which was then analyzed using the 3 steps of the Miles, Huberman, and Saldana model: data condensation, data display, and conclusions drawing. The result of this study is that the book of Nahwu Wadhih First Juz is a book for elementary school, which is the work of 2 experts in Egypt, namely Dr. 'Ali Al-Jarim and Dr. Musthafa Amin. This book contains basic rules in Arabic that aim to help beginners learn the rules of Arabic properly and correctly. This book has several advantages but is also inseparable from its shortcomings. Further research could be conducted to study the effectiveness of using this book in the Arabic language learning process in different educational institutions.